Analisis Kondisi Fisik Atlet Junior Taekwondo Dojang TTC Kandora Kabupaten Tana Toraja - Hasyim; Awaluddin; Milkha Tambirang (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
This research aims to analyze the condition of the Dojang Taekwondo Junior TTC Kandora Tana taekwondo athletes, Toraja Regency. The type of research used is Quantitative Descriptive. The method used is a survey method with test and measurement techniques. The variable in this research is the physical condition of the Junior Taekwondo Athlete Taekwondo Dojang TTC Kandora Tana Toraja Regency. The population sampling technique (all population participants as research samples) consisted of 18 participants. The instruments used are the Strength Test with Upright Jumping, Speed ​​Test with 20 Meter Running (Sprint), Flexibility Test with split test, and Endurance Test with Push Ups. The data analysis technique used is Descriptive Statistics using statistical analysis with the help of SPSS (Statistical Passage For Social Science) version 25.0. Based on the initial data and research data obtained and referring to each discussion, it can be concluded that the physical condition of the Dojang TTC Kandora Junior Taekwondo Athlete, Tana Toraja Regency is in the medium category when viewed from the percentage. The results of the research show that the physical condition of the Dojang TTC Kandora Tana Junior Taekwondo Athlete, Toraja Regency as a whole can be explained, namely that of the 18 participants, 0 participants got a very good score with a percentage of 0%, 7 participants got a good score with a percentage of 38.9%, and a score of medium at 0%. 11 participants with a percentage of 61.1%, less than 0 participants with a percentage of 0%.